The orientation of galaxy pairs with filamentary structures: Dependence on morphology - Mesa, Valeria Alejandra (2018)
Aims. With the aim of performing an analysis of the orientations of galaxy pair systems with respect to the underlying large-scale structure, we study the alignment between the axis connecting the pair galaxies and the host cosmic filament where the pair resides. In addition, we analyze the dependence of the amplitude of the alignment on the morphology of pair members as well as filament properties. Methods. We build a galaxy pair catalog requiring rp < 100 h-1 kpc and ΔV < 500 km s-1 within redshift z < 0.1 from the Sloan Digital Sky Survey (SDSS). We divided the galaxy pair catalog taking into account the morphological classification by defining three pair categories composed by elliptical-elliptical (E-E), elliptical-spiral (E-S) and spiral-spiral (S-S) galaxies. We use a previously defined catalog of filaments obtained from SDSS and we select pairs located closer than 1 h-1 Mpc to the filament spine, which are considered as members of filaments. For these pairs, we calculate the relative angle between the axis connecting each galaxy, and the direction defined by the spine of the parent filament. Results. We find a statistically significant alignment signal between the pair axes and the spine of the host filaments consistent with a relative excess of ∼15% aligned pairs. We obtain that pairs composed by elliptical galaxies exhibit a stronger alignment, showing a higher alignment signal for pairs closer than 200 h-1 kpc to the filament spine. In addition, we find that the aligned pairs are associated with luminous host filaments populated with a high fraction of elliptical galaxies. The findings of this work show that large-scale structures play a fundamental role in driving galactic anisotropic accretion as induced by galaxy pairs exhibiting a preferred alignment along the filament direction.